INTRODUCTION OF INTERACTIVE LEARNING IN PRIMARY SCHOOL PRACTICE - L.R. Shpachuk; M.V. Vovk (Academy of Cognitive and Natural Sciences, 2010)
The ways of introduction of the interactive teaching are exposed in the article, essence of the interactive teaching is lighted up; the groups of interactive methods of teaching are described.